Kallistatin Attenuates Experimental Autoimmune Uveitis by Inhibiting Activation of T Cells - Muhammad, Fauziyya; Avalos, Priscilla N.; Mursalin, M. H.; Ma, Jian-Xing; Callegan, Michelle C.; Lee, Darren J. (Frontiers in Immunology, 2020)
Experimental autoimmune uveoretinitis (EAU) is a mouse model of human autoimmune uveitis. EAU spontaneously resolves and is marked by ocular autoantigen-specific regulatory immunity in the spleen. Kallikrein binding protein (KBP) or kallistatin is a serine proteinase inhibitor that inhibits angiogenesis and inflammation, but its role in autoimmune uveitis has not been explored. We report that T cells activation is inhibited and EAU is attenuated in human KBP (HKBP) mice with no significant difference in the Treg population that we previously identified both before and after recovery from EAU. Moreover, following EAU immunization HKBP mice have potent ocular autoantigen specific regulatory immunity that is functionally suppressive.